Analisis Pemahaman Konsep Gerak Parabola melalui Media Pembelajaran Berbasis Sensor dengan Pendekatan Inkuiri: Analisis Pemahaman Konsep Gerak Parabola melalui Media Pembelajaran Berbasis Sensor dengan Pendekatan Inkuiri - Muhammad Aldi Aulia Fathurohman; M Afif Rizky A; Hasan Amin (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
This study aims to improve students’ understanding of the concept of parabolic motion through the development of technology-based learning media. Parabolic motion is often difficult to understand because it is abstract and requires a deep understanding of the relationship between physical variables, such as initial velocity, launch angle, maximum height, and horizontal reach. To overcome this, a sensor-based teaching aid was developed by integrating infrared technology and an Arduino microcontroller. This tool allows real-time measurement of physical variables of parabolic motion, so that students can directly observe the relationship between variables. An inquiry-based approach was also applied to encourage students to be actively involved in data exploration and analysis. The research process involved tool design, trials, and data analysis conducted on students of Madrasah Aliyah Al-Musdariyah Cileunyi. The results showed that this teaching aid was effective in visualizing parabolic trajectories concretely. The trial data showed an increase in maximum height from 0.65 m to 0.78 m and horizontal reach from 1.23 m to 1.54 m along with an increase in initial velocity. In addition to improving students’ conceptual understanding, the combination of teaching aids and inquiry approaches also succeeded in developing their critical and analytical thinking skills. With this approach, students can see the application of physics concepts in real life, which increases their motivation to learn. This study recommends the integration of teaching aids with data analysis software to facilitate data processing and develop similar modules for other physics materials. Thus, the results of this study provide significant contributions to technology-based physics learning, making abstract concepts more accessible and understandable to students.